Predictors of thickened carotid intima media thickness among well controlled lupus nephritis patients in a Malaysian tertiary centre - N.CT. Kong; M.S. Mohamed Said; S.S. Shaharir (Reumatismo, 2012)
Objectives. To investigate the prevalence of thickened carotid intima media thickness (CIMT) and its associated risk factors in patients with lupus nephritis (LN) who were in remission. Methods. This was a cross sectional study in which consecutive LN patients who were in remission and attending our Nephrology/SLE Clinic were included. Their demographic profile, traditional cardiovascular risk factors and treatment medications were evaluated by clinical interview and review of medical records. Carotid intima media thickness (CIMT) was measured using B Mode carotid ultrasonography. CIMT was considered to be abnormally thickened if it exceeded the 75th percentile matched for age-and sex-matched normal controls. The associated factors for thickened CIMT were examined. Results. A total of 39 patients with a mean remission duration of 29±24.3 months and on a mean prednisolone dose of 9.10±7.83 mg daily completed the study. Six patients (15.4%) had thickened CIMT. On univariate analysis, male gender, patient age, older age at diagnosis, higher serum CRP levels, greater proteinuria and higher mean cumulative azathioprine dose were associated with thickened CIMT (P<0.05). Lower mean cumulative doses of cyclosporine A (CyA) and mycophenolic acid (MPA) (P<0.05) each were associated with thickened CIMT. Using regression analysis, the associated factors of CIMT were older age at diagnosis and proteinuria. Conclusions. Lupus factors particularly age at diagnosis and proteinuria were the associated factors of thickened CIMT. Larger prospective trials are indicated to confirm our findings.